2006
DOI: 10.1128/jcm.44.5.1899-1902.2006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Loop-Mediated Isothermal Amplification Method for Rapid Diagnosis of Bordetella pertussis Infection

Abstract: We developed a loop-mediated isothermal amplification (LAMP) method to detect Bordetella pertussis infection. This LAMP assay detected B. pertussis with high sensitivity, but not other Bordetella species. Among nasopharyngeal swab samples from subjects with suspected pertussis, LAMP results showed a high level of agreement with results of conventional PCR. This method is a rapid, sensitive, and specific method for diagnosis of B. pertussis infection even in clinical laboratories with no specific equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 25 publications
3
66
0
4
Order By: Relevance
“…LAMP is a nucleic acid amplification method that was developed in Japan as a simple, easy, and fast assay used to detect B. pertussis DNA (3,5). In our study, all 57 cases of microbiologically confirmed B. pertussis infections were LAMP-positive, while only 60z were culture-positive.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…LAMP is a nucleic acid amplification method that was developed in Japan as a simple, easy, and fast assay used to detect B. pertussis DNA (3,5). In our study, all 57 cases of microbiologically confirmed B. pertussis infections were LAMP-positive, while only 60z were culture-positive.…”
Section: Discussionmentioning
confidence: 73%
“…Primers for the LAMP assay were designed on the basis of PT promoter region of the B. pertussis strain Tohama (genome position, 159549-159755; GenBank accession number: BX640422). This assay demonstrated a high agreement level with conventional polymerase chain reaction (PCR) results (3).…”
Section: Methodsmentioning
confidence: 88%
“…Compared with the culture method, nucleic acid amplification tests such as the IS481-based real-time polymerase chain reaction (PCR) and B. pertussis-specific loop-mediated isothermal amplification (LAMP) are highly sensitive for the detection of B. pertussis DNA (17)(18)(19). Therefore, these nucleic acid amplification tests have been recommended for the accurate diagnosis of pertussis (20).…”
Section: Introductionmentioning
confidence: 99%
“…LAMP is a very simple and fast procedure that does not require specific equipment. It has a high sensitivity and specificity because the LAMP primers target eight regions in approximately 200 nucleotides (4). Results are obtained within 1 hour, inclusive DNA extraction and genome amplification steps.…”
mentioning
confidence: 99%
“…In the present study, bacterial isolation and loopmediated isothermal amplification (LAMP) for the detection of B. pertussis genomic DNA were tested, using a primer set reported by Kamachi et al (4). The test subjects consisted of 43 patients aged <15 years who were suspected to have pertussis and were treated at the Saiseikai Central Hospital, Tokyo in 2010 and 2011.…”
mentioning
confidence: 99%